The Effect of Liquidity Management, Cost Structure, and Leverage Policy on Financial Performance in the Retail Sector in Jakarta - Yanti Budiasih; Deni Iskandar (West Science Accounting and Finance, 2024)
This study examines the effect of liquidity management, cost structure, and leverage policy on the financial performance of retail sector companies in Jakarta. Utilizing a quantitative approach, primary data were collected from 165 respondents using a structured questionnaire measured on a Likert scale of 1-5. Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) was employed to analyze the relationships between the independent variables—liquidity management, cost structure, and leverage policy—and the dependent variable, financial performance. The findings indicate that all three factors significantly and positively influence financial performance, with leverage policy showing the strongest effect. The study underscores the importance of strategic financial management practices for retail companies to enhance profitability and sustain competitive advantages. Practical implications include adopting efficient liquidity tools, optimizing cost structures, and strategically managing leverage to maximize growth and stability.